2017
DOI: 10.19128/turje.329755
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of PISA 2015 achievements of OECD countries within income distribution and education expenditures

Abstract: The purpose of this study was to investigate the relationships between student achievement, income distributions and education expenditures in the member countries of Organisation for Economic Cooperation and Development (OECD). The study was based on literature review and its data were gathered from OECD sources to a large extent. In the study, current student achievements of the member countries were expressed with PISA 2015 scores. The study revealed that income inequality was one of the variables influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…On the other hand, a study by Yurttaş Kumlu (2018) showed that usage of information and communication technologies had a positive impact on Performance in PISA. According to Yorulmaz, Çolak, and Ekinci (2017), student performance was related to justice and effectiveness in usage of educational resources rather than amount of them, which was concluded with an analysis of PISA 2015 dataset.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study by Yurttaş Kumlu (2018) showed that usage of information and communication technologies had a positive impact on Performance in PISA. According to Yorulmaz, Çolak, and Ekinci (2017), student performance was related to justice and effectiveness in usage of educational resources rather than amount of them, which was concluded with an analysis of PISA 2015 dataset.…”
Section: Introductionmentioning
confidence: 99%
“…They found a positive and statistically significant relationship between GDP per capita and PISA scores, but spending on education was found to be statistically insignificant. Yorulmaz, Colak, and Ekinci (2017) studied the relationship between PISA 2015 scores and income inequality. Their results suggested income inequality was one of the variables influencing the PISA achievements of students, but several countries with high-income inequality scored above average results, nonetheless.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the 1970s, scholars have been interested in the topic of teacher autonomy and initially attempted to define the concept (Samuels, 1970). With teacher quality coming into prominence in determining education quality (Yorulmaz et al, 2017) and student success (Organization for Economic Co-operation and Development (OECD, 2016b), the number of studies on teacher autonomy has increased significantly. This growing body of literature has necessitated a systematic review of the subject.…”
Section: Introductionmentioning
confidence: 99%